2022
DOI: 10.1128/msystems.01248-21
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gut Microbiome Meta-analysis Reveals Alterations in Carbohydrate Metabolism in Response to Aging

Abstract: Aging-associated microbial alteration is hypothesized to play an important role in host health and longevity. However, investigations regarding specific gut microbes or microbial functional alterations associated with aging have had inconsistent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
12
1
Order By: Relevance
“…Relevant studies reanalyzing murine gut microbiome datasets have also described consistent microbial structure alterations in the setting of a known mouse model that induces obesity and metabolic alterations (the "high-fat diet" model) (Bisanz et al, 2019) and during aging (You et al, 2022). These meta-analyses have also revealed that each study has a marked influence on the microbial structure, but this did not seem to alter the reproducibility of the microbial alterations observed with the experimental model or variable of interest.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Relevant studies reanalyzing murine gut microbiome datasets have also described consistent microbial structure alterations in the setting of a known mouse model that induces obesity and metabolic alterations (the "high-fat diet" model) (Bisanz et al, 2019) and during aging (You et al, 2022). These meta-analyses have also revealed that each study has a marked influence on the microbial structure, but this did not seem to alter the reproducibility of the microbial alterations observed with the experimental model or variable of interest.…”
Section: Discussionmentioning
confidence: 92%
“…These findings raise an interesting aspect regarding the conserved ability of the LIP model to trigger shifts in periodontal microbial structure across studies, an aspect we could infer from the literature but, due to important differences in bioinformatic analyses, was difficult to ascertain and visualize. Relevant studies reanalyzing murine gut microbiome datasets have also described consistent microbial structure alterations in the setting of a known mouse model that induces obesity and metabolic alterations (the “high‐fat diet” model) (Bisanz et al., 2019) and during aging (You et al., 2022). These meta‐analyses have also revealed that each study has a marked influence on the microbial structure, but this did not seem to alter the reproducibility of the microbial alterations observed with the experimental model or variable of interest.…”
Section: Discussionmentioning
confidence: 97%
“…The murine gut microbiome changes with aging and is associated with alterations in microbial carbohydrate metabolism, decreased fecal short-chain fatty acids and decreased cobalamin and biotin biosynthesis [ 60 , 61 ]. In the current study, we examined well-known gut-derived uremic toxins that are generated in the CKD milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the gut microbiota of the same genotype of mice from two different vendors differed in their gut microbiome profile (Hufeldt et al, 2010). Leveraging the use of publicly available 16S rRNA gene sequencing data, a study performed a meta-analysis on the effect of aging on the gut microbiome in mice (You et al, 2022). However, a significant limitation of this study was the differences in methods between the studies and the relatively small sample size (You et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the use of publicly available 16S rRNA gene sequencing data, a study performed a meta-analysis on the effect of aging on the gut microbiome in mice (You et al, 2022). However, a significant limitation of this study was the differences in methods between the studies and the relatively small sample size (You et al, 2022). Although important, these studies did not consider the multitude of other factors that, combined, may influence, and confound the gut microbiome in animal facilities.…”
Section: Introductionmentioning
confidence: 99%